Predicting phonon scattering and tunable thermal conductivity of 3D pillared graphene and boron nitride heterostructure - Karimzadeh, Sina; Safaei, Babak; Jen, Tien-Chien (Pergamon-Elsevier Science Ltd, 2021)
In this work, we have studied the transfer of phonon energy in hybrid structure of pillared graphene and boron nitride film. The obtained results showed that, due to the occurrence of ballistic transfer with the elongation of heterostructure, thermal conductivity was increased. We also found that the amount of interfacial thermal conductivity was changed by changing the direction of thermal flux and the application of thermal flux along the direction of pillared graphene nanostructure was more favorable. We observed that increase of temperature from 100 to 700 K increased the amounts of interfacial thermal conductance (ITC) in C-N and C-B models by 19 and 10%, respectively. Since defects are inevitable during the fabrication and growth of these structures, in this work, we investigated the concentration and arrangement of these defects at joint interface and found that increase of defect concentration decreased thermal flux and ITC and also type of defects had a significant effect on thermal rectification. Also, the detection of these defects in a controlled manner can help making thermal conductivity tunable. We evaluated the effect of tensile from 0 to 10% in heterostructure with and without vacancy defects and found that ITC was decreased by 45% and 30% and temperature jump was increased by 80% and 45% at interface, respectively. In addition, to further analyze the obtained results, phonon vibration power spectra were also examined. Finally, by using Von Mises stress criterion, stress distribution and concentration through sheets and interface in the presence of mechanical strains and various defects were investigated. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Thermal conductivity; Phonon energy; NEMD; PGN and h-BN heterostructures